Respuesta :
Answer:
y = 1 and y = 5
Step-by-step explanation:
[tex]( 3 y -9)^2 + 7 = 43\\\\((3y)^2 + (-9)^2 + 2(3y)(-9)) = 43 - 7\\\\(9y^2 + 81 -54y) = 36\\\\9y^2 -54y + 81 -36 = 0\\\\9y^2 -54y + 45 = 0\\\\9(y^2 -6y + 5) = 0\\\\y^2 - 6y + 5 = 0\\\\y^2 - 5y - y + 5 = 0\\\\y(y - 5) -1(y - 5 ) = 0 \\\\( y - 1 )( y - 5) = 0\\\\y = 1 \ , \ y = 5[/tex]
The values of y in the equation (3y-9)^2+7 = 43 are 1 and 5
How to solve for y?
The equation is given as:
(3y-9)^2+7 = 43
Subtract 7 from both sides of the equation
(3y - 9)^2 = 36
Take the square root of both sides
3y - 9 = ±6
Add 9 to both sides
3y = 9 ± 6
Divide through by 3
y = 3 ± 2
Expand
y = (3 - 2 or 3 + 2)
Evaluate
y = 1 or 5
Hence, the values of y are 1 and 5
Read more about quadratic equations at:
https://brainly.com/question/1214333
#SPJ6